Wirkungsevaluation mobiler Jugendarbeit Methodische Zugänge und empirische Ergebnisse - Mayrhofer, Hemma (Verlag Barbara Budrich, 2017)
Mobile youth work is a social support service for a particularly vulnerable target group. The present study on four institutions of mobile youth work in Austria captured the high complexity of the dynamics and interrelations of effects in this field of intervention through a complex research design and a mix of five methodological approaches. Each research approach was characterised by special strengths that complemented each other and made particularly meaningful impact findings possible.